FILOSOFIYALÍQ KÓZQARASLAR EVOLYUCIYASÍNÍŃ BILIMLENDIRIW TARAWÍNA TÁSIRI - Allaniyazov, I.B. (SCIENCE and SOCIETY, 2025)
The article discusses the influence of philosophical evolution on the education system. At the same time, the views of philosophical scientists and teachers on the system and theory of pedagogy are taken into account. Ideas are discussed is about transition in education to self-education, in training to self-education, in upbringing to self-education, etc.
Keywords: pedagogy; system; development; development of personality; formation; teaching; training; socialization; theory; independence